TD-DFT calcalution of BODIPYand related compunds as photoseners for Photodynamic therapy (Damascus University Journal for the basic sciences, 2022)
In this work we carrid out Theoretical evaluation of Bodipy and related as photosensitizer for use in photodynamic therapy (PDT).Five compounds were studied through substituents at the position 6 in the chromophore of Bodipy with elements from the fifth column in the Periodic table such(N-P-As-Bi).in the present study the density functional theory and its time dependent extension calculations have been used to calculate the eneregy of ground and singlet -triplets excited states, energy differences     , electronic absorption spectra , transition dipole moments (TDM) for spin-allowed S0→Sn and other proporities
Keywords: Bodipy; photosenstizers; PDT; TD-DFT; ground state; excited state